Islamic Sexuality Education to Prevent Sexual Violence in Higher Education: Lessons from Universitas Brawijaya - Nur Chanifah; Putri Ghoida Habibillah; Ria Anjani; Abu Samsudin (Pustaka Peradaban, 2025)
Sexual violence remains a persistent challenge in university environments, despite the implementation of various policies and task forces, including at Universitas Brawijaya. This study investigates the integration of fiqh sexuality in preventing sexual violence on campus. Employing a qualitative case study with a socio-legal approach, data were gathered through in-depth interviews, observations, and documentation of the Universitas Brawijaya's PPKS Task Force activities. The findings reveal that while educational efforts are underway, the approach predominantly focuses on legal and psychological aspects, with fiqh sexuality not yet systematically integrated. Crucially, from the perspective of maqāṣid al-syarī'ah, fiqh sexuality offers significant potential for preventing sexual violence through the principles of ḥifẓ al-nafs, ḥifẓ al-nasl, and ḥifẓ al-'aql. Therefore, mainstreaming fiqh sexuality education is essential in university sexual violence prevention strategies.